The Legalization of Abortion and Subsequent Youth Homicide: A Time Series Analysis - Berk, Richard (Analyses of social issues and public policy, 2003)
In this article, we examine the association between the legalization of abortion with the 1973 Roe v. Wade decision and youth homicide in the 1980s and 1990s. An interrupted time series design was used to examine the deaths of all U.S. 15- to 24-year-olds that were classified as homicides according to the International Classification of Diseases (codes E960-969) from 1970 to 1998. The legalization of abortion is associated over a decade later with a gradual reduction in the homicides of White and non-White young men. The effect on the homicides of young women is minimal. We conclude that the 1990s decline in the homicide of young men is statistically associated with the legalization of abortion. Findings are not consistent with several alternative explanations, such as changes in the crack cocaine drug market. It is almost inconceivable that in the United States of today, policies affecting the choice to have children would be justified as a means to control crime. Yet, if the legalization of abortion had this unintended effect, the full range of policy implications needs to be discussed